ASSOCIATION OF INFLAMMATION DEGREE AND LENGTH OF STAY AFTER LOWER GASTROINTESTINAL SURGERY IN INTENSIVE CARE - Salsabila Al-Fatih Panur; Faisal Sommeng; Farah Ekawati Mulyadi; Agung Kurniawan; Fendy Dwimartyono (International Medical Journal Corp. Ltd, 2026)
Background: Lower gastrointestinal surgery induces a systemic inflammatory response that may influence patient recovery and duration of care. The Systemic Immune-Inflammation Index (SII) is considered a practical inflammatory marker reflecting the balance between immune and inflammatory responses. Objective: To analyze the association between inflammation degree and length of stay in patients after lower gastrointestinal surgery treated in the intensive care unit. Methods: This was an analytic observational study with a cross-sectional approach using secondary data from medical records of patients at Ibnu Sina YW-UMI Hospital in 2025. Samples were taken using total sampling, yielding 30 patients who met the study criteria. Inflammation degree was categorized based on SII values into low and high, while length of stay was categorized as short (3-5 days) and prolonged (≥6 days). The association was analyzed using the Spearman test. Results: The majority of patients were male (16; 53.3%), aged ≥50 years (19; 63.3%), and were most frequently diagnosed with rectal cancer and rectal adenocarcinoma, 12 patients each (40.0%). A total of 18 patients (60.0%) had high SII, while 22 patients (73.3%) had a short length of stay. The Spearman test showed a correlation coefficient of 0.339 with p=0.067. Conclusion: Inflammation degree was not significantly associated with length of stay in patients after lower gastrointestinal surgery treated in the intensive care unit. These findings suggest that length of stay is likely also influenced by other clinical factors beyond inflammation, and further research is still needed to predict hospital stay duration related to the inflammatory response occurring during surgery.